MUSIK BAMBU BANYUMAS - Saryoto, S.Kar., M.Hum. (LP2M ISBI Bandung, 2018)
Bamboo music will not become a musical identity of an area, if it is not related to the inherent culture and creativity of the supporting community. Likewise the life of bamboo music in Banyumas, has recently experienced a change when compared to several decades before. Therefore, the presentation of bamboo music in Banyumas can be assumed to have work on creativity and be able to do musical dialogue with the community, so that their lives up to now still survive and compete with other types of art. To see this, a multidisciplinary approach can be used as a paradigm in observing it, including examining what and how bamboo music is in Banyumas; especially those related to the culture and creativity of the people. Bamboo music as the identity of the Banyumas community, is still living in accordance with the dynamics of the supporting community. For this reason, it is necessary to examine various factors that support this bamboo music life, especially those in the Banyumas cultural area.